Field performance and new uses of rapid influenza testing in Thailand - Simmerman, James Mark; Chittaganpitch, Malinee; Erdman, Dean; Sawatwong, Pongpun; Uyeki, Timothy M.; Dowell, Scott F. (International journal of infectious diseases, 2007)
Rapid influenza tests are increasingly used in surveillance systems and for clinical care in Southeast Asia. However, the performance and utility of rapid influenza tests under field conditions in rural Southeast Asia has not been evaluated. In the context of a larger study on the causes of respiratory illness in rural Thailand, we used a rapid test to collect data on influenza burden, seasonality, and cost of illness. We compared the performance of the QuickVue ® Influenza Test to tissue cell viral culture and reverse transcriptase-polymerase chain reaction (RT-PCR) among 1092 Thai patients meeting the World Health Organization case definition for influenza-like illness over a 12-month period. The sensitivity and specificity of the QuickVue test compared to viral culture were 77% and 96%, respectively. Rapid influenza tests were useful to describe the seasonality of influenza, estimate the cost of illness, increase the sensitivity of surveillance, conduct outbreak responses, and guide evaluation of suspected avian influenza virus infections. Despite their high cost, rapid influenza diagnostic tests are useful tools for influenza research, surveillance, and outbreak investigations in Southeast Asia.